Business plan for an innovative leisure centre: OF’KIDS - Fernandes, Vera Lúcia Tinoco (2015)
This master's project aims to develop a business plan at the strategic and operational level in order to support the creation of an innovative space dedicated to children and young people, where they can have access to different areas of entertainment and also study and education, following the values and tradition of UPAJE. It is expected that this space is opened in July 2015. In order to study the feasibility of the project and what value does it bring to UPAJE, a study at a strategic and operational level will make it possible to assess the impact of this new business unit and what resources are necessary for its implementation and evaluation. An analysis of the current main market in which UPAJE operates was carried out: Summer Camps, and also an analysis of the new segment and its potential competitors. Next, a brief internal review was performed, in order to understand the current position of UPAJE in the market. Then it was possible to prepare a marketing plan and a management plan, also through the financial analysis in order to assess the feasibility of the new business.